Research progress on risk factors related to intracranial artery, carotid artery, and coronary artery stenosis - Liu, Ruijun; Shao, Jing (Frontiers in Cardiovascular Medicine, 2022)
In recent decades, with the rapid development of economy, the acceleration of social aging and urbanization, and the prevalence of unhealthy lifestyles, the number of patients with cardiovascular and cerebrovascular diseases has shown an increasing trend year by year. It has also become one of the important causes of disability and death in all ages and groups. Atherosclerosis is the main pathological change of ischemic cardiovascular and cerebrovascular diseases, which mainly invades the large and medium arteries of the body circulation. In particular, cerebral artery and coronary artery lesions have the most significant impact on life. There is the same pathogenic mechanism between intracranial and extracranial arteries and coronary atherosclerosis, so there is a certain relationship between the degree of atherosclerosis. In this paper, the risk factors related to intracranial and extracranial arteries and coronary artery stenosis were reviewed. It provides a theoretical basis for early detection, early diagnosis and early treatment of intracranial and extracranial artery and coronary artery stenosis to reduce the occurrence and development of cardiovascular and cerebrovascular diseases.